THE IMPACT OF GOVERNMENT SPENDING, THE AMOUNT OF ZAKAT DISTRIBUTION, AND GENDER EQUALITY ON THE GINI INDEX IN ACEH - Syifa Zhafira, Cut Amanda; Sari, Nilam; Dian Safitri, Winny (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2026)
Regional development success is reflected not only in economic growth but also in the degree of income distribution equality. Aceh represents a unique institutional setting characterized by strong Islamic values, substantial fiscal transfers, and significant zakat potential. Nevertheless, income inequality in the province has continued to fluctuate, raising questions about the effectiveness of fiscal and Islamic redistributive instruments. This study examines the effects of government expenditure, zakat distribution, and gender equality on income inequality in Aceh, measured by the Gini index.This research employs an explanatory quantitative approach using panel data from districts and municipalities in Aceh Province during 2020–2024. Multiple linear regression with the Fixed Effect Model (FEM) is applied to account for regional heterogeneity. The results show that government expenditure and zakat distribution have negative but statistically insignificant effects on income inequality, indicating that their redistributive roles have not yet been fully effective. In contrast, the Gender Development Index (GDI) has a negative and statistically significant effect, suggesting that improvements in gender equality contribute to reducing income disparities. Simultaneously, the three variables significantly influence income inequality, although the model explains a moderate proportion of its variation (R² = 0.518567). These findings underscore the importance of strengthening fiscal effectiveness, optimizing zakat governance, and promoting gender-inclusive development to achieve more equitable economic outcomes in Aceh.